DETEKSI REGULASI EMOSI SISWA DALAM PENCAPAIAN KEMAMPUAN PEMAHAMAN KONSEP PADA SISWA PKBM PAKET C - leila aseana (Universitas PGRI Semarang, 2020)
This study aims to describe the process of detection of emotional regulation ofstudents in achieving the ability to understand concepts in PKBM studentsPackage C. Data collection was done by questionnaire and Mathematics ConceptUnderstanding tests. This research is an analytical survey with Crossectionalapproach, the sample is taken by purposive sampling technique that is as manyas 3 respondents. The instruments used in this study were questionnaire and testresult sheet. This study is recommended to find out the regulation of emotions inachieving the ability of students to understand concepts in PKBM Package CKeywords: Emotion regulation, concept understanding